The influence of chatbot interaction and chatbot problem solving on user satisfaction in Surabaya city mediated by accuracy on Shopee e-commerce in Indonesia - Christopher Wijaya; Mohamad Trio Febriyantoro (Jurnal Mantik, 2026)
This study examined the effect of chatbot interaction and chatbot problem-solving on user satisfaction in Shopee e-commerce in Surabaya, with accuracy as a mediating variable. The research applied a quantitative approach using questionnaire data collected from 235 Shopee users who had interacted with the Shopee chatbot. The data were examined using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicated that chatbot interaction and chatbot problem-solving had positive and significant effects on accuracy. Furthermore, both chatbot interaction and chatbot problem-solving directly influence customer satisfaction positively and significantly. Accuracy also had a significant positive effect on customer satisfaction. Mediation analysis showed that accuracy significantly mediated the relationship between chatbot interaction and customer satisfaction, as well as between chatbot problem-solving and customer satisfaction. These findings demonstrated that the quality of interaction and the effectiveness of chatbot problem-solving enhanced perceived accuracy, which subsequently increased user satisfaction. The study contributed to the understanding of AI-based customer service performance in the e-commerce context and highlighted the importance of improving chatbot accuracy to optimize user satisfaction. Practical implications suggest that Shopee should strengthen chatbot knowledge systems and response precision to ensure reliable and satisfying customer experiences